Amorphous Domains in Black Titanium Dioxide - Kang, Jianxin; Zhang, Yan; Chai, Ziwei; Qiu, Xiaoyi; Cao, Xingzhong; Zhang, Peng; Teobaldi, Gilberto; Liu, Li‐Min; Guo, Lin (Advanced materials (Weinheim), 2021)
Although oxygen vacancies (Ovs) play a critical role for many applications of metal oxides, a controllable synthetic strategy for anisotropic Ovs remains a great challenge. Here, a novel strategy is proposed to achieve the regional dual structure with anisotropic Ovs at both the surface and in the interior of TiO2 by constructing amorphous domains. The as‐prepared black TiO2 with amorphous domains exhibits superior activity in degrading rhodamine B (RhB) solutions, which can instantly decompose RhB with just a shake. First‐principle simulations reveal that subsurface Ovs in TiO2 are energetically favored, resulting in the formation of amorphous domains in the interior region via diffusion of surface‐formed Ovs into the subsurface. The stable Ov‐induced amorphous domains in TiO2 with enhanced catalytic performances provide a scalable strategy to practical Ov engineering in functional metal oxides. Benefiting from the diffusion of oxygen vacancies from the surface to inside, the regional dual structure with anisotropic oxygen vacancies at both the surface and in the interior of TiO2 is obtained by constructing amorphous domains. The as‐prepared sample exhibits superior catalytic activity, which can immediately degrade rhodamine B solution to colorless with a shake.